Attitude Toward Euthanasia Scale: Psychometric Properties and Relations With Religious Orientation, Personality, and Life Satisfaction. (December 2013) - Aghababaei, Naser; Wasserman, Jason Adam
End-of-life decisions (ELDs) represent a controversial subject, with ethical dilemmas and empirical ambiguities that stand at the intersection of ethics and medicine. In a non-Western population, we examined individual differences in perceiving ELDs that end the life of a patient as acceptable and found that an attitude toward euthanasia (ATE) scale consists of 2 factors representing voluntary and nonvoluntary euthanasia. Also, acceptance of ELDs that end the life of a patient negatively correlated with life satisfaction, honesty–humility, conscientiousness, and intrinsic and extrinsic personal motivation toward religion. These findings provided additional construct validity of the ATE scale.